Management of Neuraxial Analgesia in a Parturient with Factor XIII Deficiency: A Case Report and Proposed Management Algorithm - David B. Carroll; Conrad Myler; Natthapol Songdej; Khaled Sedeek; Dmitri Bezinover (Case Reports in Anesthesiology)
Factor XIII (FXIII) deficiency is a rare coagulation defect that can be associated with significant bleeding. A 28-year-old pregnant woman, with a history of hemorrhagic stroke secondary to severe congenital FXIII deficiency, presented in active labor requesting an epidural. Factor XIII levels had been monitored throughout her pregnancy and treated with intermittent factor XIII infusions to maintain factor levels above 30% of normal. After careful multidisciplinary peripartum evaluation and FXIII replacement, neuraxial analgesia was performed without complication. Neuraxial analgesia can be performed without complication in patients with FXIII deficiency if FXIII levels are carefully managed and no other coagulopathy exists.